2020
DOI: 10.1177/1847980420955093
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the structural and electronic properties of MoxTi1−xS2 monolayers via first principle simulations

Abstract: Two-dimensional transition metal dichalcogenides have gained great attention because of their peculiar physical properties that make them interesting for a wide range of applications. Lately, alloying between different transition metal dichalcogenides has been proposed as an approach to control two-dimensional phase stability and to obtain compounds with tailored characteristics. In this theoretical study, we predict the phase diagram and the electronic properties of Mo xTi1− xS2 at varying stoichiometry and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…3.a that this material has a semi-metal composition because the valence band maximum is at the (0,0,0) point and the conduction band minimum is at the L (1/2,0,1/2) point with a band gap of 0.05 eV. This result agrees with the results of the ab-initio calculation done by [13], and [33]. While TiS2 was supposed to have a semi-conductor character and an indirect gap of about 1.9 eV, according to Allan et al [7] A metallic character is observed for TiSe2 and TiTe2 which show an overlap of the valence and conduction band (Fig.…”
Section: Resultssupporting
confidence: 86%
“…3.a that this material has a semi-metal composition because the valence band maximum is at the (0,0,0) point and the conduction band minimum is at the L (1/2,0,1/2) point with a band gap of 0.05 eV. This result agrees with the results of the ab-initio calculation done by [13], and [33]. While TiS2 was supposed to have a semi-conductor character and an indirect gap of about 1.9 eV, according to Allan et al [7] A metallic character is observed for TiSe2 and TiTe2 which show an overlap of the valence and conduction band (Fig.…”
Section: Resultssupporting
confidence: 86%
“…These superior properties make TMDCs a promising new materials for innovative sensors, optoelectronic devices, highly sensitive photodetection, quantum communication devices, and so on. [15][16][17][18][19] Recently, black phosphorus photodetector has been demonstrated that it can operate under bias with a very low dark current and attain an intrinsic responsivity up to 135 mA W À1 and 657 mA W À1 in 11.5 nm and 100 nm thick devices at room temperature. 20 With the advent of the post molar era, there is a growing demand for nanodevices with high response and sensitivity.…”
Section: -13mentioning
confidence: 99%
“…For photonic applications, it is required to develop 2D materials with continuous tunable bandgaps, and doping is one of the best techniques that can be exploited for this purpose [19]. Substitutional defects in a pristine monolayer may lead to a change in the lattice structure of the host material, resulting in a wide range bandgap tunability [20,21]. In our recent work [22], we defected 2D InSe with different substitutional impurities to generate well-defined and sharp defect states within the bandgap of the material, and we showed the possibility of using these new energy levels to achieve efficient emissions of single photons [23,24].…”
Section: Introductionmentioning
confidence: 99%